Quality of life (QOL) of patient wearing removable denture after taking treatment in polyclinic, Kulliyyah of Dentistry, IIUM - Ramli, Nur Erwanie; Mohd Noor, Nur Ain Nabilla; Zulkifli, Karimah Wahida (Kulliyyah of Dentistry, International Islamic University Malaysia, 2022)
This study aimed to measure Oral Health quality of life (OH-QoL) of patients wearing removable dentures. A cross sectional descriptive and analytical study was carried out using validated Malay translated Oral Health Impact Profile (OHIP) questionnaires to assess OHQoL among 164 patients who had received removable dentures from January 2012 until December 2014 at Polyclinic, Kulliyyah of Dentistry, IIUM. Telephone interview method was applied to collect data. Functional limitation, physical discomfort and social disability of patients affected by the denture were included in OHIP which was presented by frequency tables. Influences of gender and type of dentures on OHIP were analyzed by X2 test and independent sample “t” test. Among total 164 patients, male and female ratio was 1:1. Female patients are wearing more removable complete denture than male (56.2% vs 43.8%) while male patients are more wearing removable partial dentures than female (54% vs 46%). More of the patients with removable partial dentures were rarely affected by their Oral Health related QoL than those with removable complete denture (61.1% vs 38.9%); however, types of dentures and OHQoL relationship was not significant. Although, more female patients mentioned that their OHQoL are rarely affected by wearing denture than their counterpart (52.1% vs 47.9%), this difference was also not significant (p>0.05). In conclusion, wearing removable denture rarely affected OHQoL. Influences of gender and types of dentures on the OHQoL of the patients could not be proved. It may be due to limitation of data collection method used in the study and other factors.